Prevalence of metal implants among US adults aged 40 years and older - Qiu-Fu Wang; Yu-Chen Tang; Hao-Ran Liao; Miao Lei; Wei Dong; Ze-Yu Liu; Jie Hao; Zhen-Ming Hu (Scientific Reports)
Abstract Metal implants are commonly used in clinical practice. However, little is known regarding the prevalence of metal implants. Therefore, this study aimed to evaluate the prevalence of metal implants in the United States (US) among individuals aged ≥ 40 years. This study conducted a serial cross-sectional analysis of US adults aged ≥ 40 years who participated in the National Health and Nutrition Examination Survey (NHANES) (2015–2016 and 2017–March 2020). Self-reported questionnaires were used to assess whether the participants had metal implants inside their bodies. The primary outcome was the prevalence of metal implants among adults aged 40 years and older. Furthermore, weighted logistic regression analysis was employed to determine the changes in the prevalence of metal implants from 2015 to March 2020. Moreover, this study investigated the variation in metal implant prevalence by demographic factors based on the pooled NHANES cycles. All analyses were conducted based on 3,736 participants from the NHANES 2015–2016 and 6,387 participants from the NHANES 2017–March 2020. This study observed a high prevalence of metal implants among adults aged 40 and older (2015–2016: 27.23%; 2017–March 2020: 31.53%). Moreover, the results of the weighted logistic regression analysis showed that the prevalence of metal implants significantly increased from 2015 to March 2020, especially among older individuals, men, and White individuals. In addition, the results of the weighted logistic regression analysis indicated that the metal implant prevalence differed by age and race/ethnicity, in which older individuals and White individuals showed a significantly higher prevalence of metal implants than younger individuals and non-White individuals, respectively. There was a high prevalence of metal implants among US adults aged 40 and older, and the prevalence of metal implants significantly increased from 2015 to March 2020. Therefore, more attention needs to be paid to this special population, and it may be necessary to ensure accessibility and affordability and assess the potential long-term health impacts of metal implants, considering the increased prevalence of metal implants.